Love Wins [compact disc, unabridged] : A Book About Heaven, Hell, and the Fate of Every Person Who Ever Lived - Bell, Rob. 1970- (Harper Audio, 2011)
Over the ages, Christians have struggled with the concept of Heaven and Hell. Do only a select few make it into Heaven? How does God choose? Author and pastor Rob Bell examines these questions and offers a mind-easing explanation of salvation.